2021
DOI: 10.31219/osf.io/837wn
|View full text |Cite
Preprint
|
Sign up to set email alerts
|

The EWAS Catalog: a database of epigenome-wide association studies

Abstract: Epigenome-wide association studies (EWAS) seek to quantify associations between traits/exposures and DNA methylation measured at thousands or millions of CpG sites across the genome. In recent years, the increase in availability of DNA methylation measures in population-based cohorts and case-control studies has resulted in a dramatic expansion of the number of EWAS being performed and pub-lished. To make this rich source of results more accessible, we have manually curated a database of CpG-trait associations… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
39
0

Year Published

2021
2021
2022
2022

Publication Types

Select...
7
2

Relationship

3
6

Authors

Journals

citations
Cited by 44 publications
(39 citation statements)
references
References 6 publications
0
39
0
Order By: Relevance
“…Using a PubMed search (using "{gene name} AND alzheimer*} as search terms) revealed that no publication exists to date directly linking any of these genes to AD. Look-up of the CpG IDs on the EWAS Catalog (http://www.ewascatalog.org/) 37 revealed that cg03073402 and cg20648333 were previously reported to be associated with aging from birth to late adolescence in blood samples 38 .…”
Section: Ewas Meta-analysis Highlights 12 Dmps Showing Experiment-wide Significant Association With Admentioning
confidence: 99%
“…Using a PubMed search (using "{gene name} AND alzheimer*} as search terms) revealed that no publication exists to date directly linking any of these genes to AD. Look-up of the CpG IDs on the EWAS Catalog (http://www.ewascatalog.org/) 37 revealed that cg03073402 and cg20648333 were previously reported to be associated with aging from birth to late adolescence in blood samples 38 .…”
Section: Ewas Meta-analysis Highlights 12 Dmps Showing Experiment-wide Significant Association With Admentioning
confidence: 99%
“…These smoking associated CpG sites could also be picking up variation from other environmental sources that are not exclusively driven by smoking, but correlated with it, such as alcohol intake. When checking in the literature for other possible associations between the 62 CpG sites and other environmental measures ( S9 Table ), 20 of these CpGs have previously been associated with age, 15 with alcohol intake or alcohol dependence, 11 with educational attainment, 10 with different types of cancer; and a few with other diseases [ 45 , 46 ]. Unlike for smoking, for most of these associations with other traits, it is unclear if they are casual, or if they could as well be driven by smoking (e.g., alcohol consumption is associated with smoking and picking up a smoking signal).…”
Section: Discussionmentioning
confidence: 99%
“…In post-hoc evaluations, we found that DMPs in PC, BTG4 and PADI1 showed trends of associations with estimated CVD risk, we identified a separate DMP in MORC2 that was associated with CRP levels ≤10 mg/L, and we successfully replicated 65 (24%) of previously reported CRP associated DMPs. All DMPs with gene annotations (13) were biologically linked to inflammation or CVD traits.…”
Section: Discussionmentioning
confidence: 99%
“…We, therefore, performed an epigenome-wide association study (EWAS) to identify differentially methylated loci associated with CRP among Ghanaians. Subsequently, we assessed whether these detected loci were associated with the 10year estimated risk of CVD in the same population, or with CVD in previous genome/epigenome-wide association studies 13,14 .…”
Section: Introductionmentioning
confidence: 99%